Prednisone for the prevention of tuberculosis-associated IRIS (randomized controlled trial): Impact on the health-related quality of life - Wouters, Edwin; Stek, Cari; Swartz, Alison; Buyze, Jozefien; Schutz, Charlotte; Thienemann, Friedrich; Wilkinson, Robert J.; Meintjes, Graeme; Lynen, Lutgarde; Nöstlinger, Christiana (Frontiers in Psychology, 2022)
Background: Tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) is an important complication in patients with HIV-associated tuberculosis (TB) starting antiretroviral treatment (ART) in sub-Saharan Africa. The PredART-trial recently showed that prophylactic prednisone reduces the incidence of paradoxical TB-IRIS by 30% in a population at high risk. This paper reports the impact of the intervention on health-related quality of life (HRQoL), a secondary endpoint of the trial, measured by an amended version of the PROQOL-HIV instrument – the instrument’s validity and reliability is also assessed. Methods: A total of 240 adult participants (antiretroviral treatment (ART)-naïve, TB-HIV co-infected with CD4 count ≤100 cells/μL) were recruited and randomized (1:1) to (1) a prednisone arm or (2) a placebo arm. In this sub-study of the PredART-trial we evaluated (1) the performance of an HIV-specific HR-QoL instrument amended for TB-IRIS, i.e. the PROQOL-HIV/TB in patients with HIV-associated TB starting ART (reliability, internal and external construct validity and invariance across time) and (2) the impact of prednisone on self-reported HR-QoL in this population through mixed models. Results: The PROQOL-HIV/TB scale displayed acceptable internal reliability and good internal and external validity. This instrument, including the factor structure with the eight sub-dimensions, can thus be applied for measuring HR-QoL among HIV-TB patients at high risk for TB-IRIS. Prophylactic prednisone was statistically significantly associated only with the ‘Physical Health and Symptoms’-subscale: a four-week course of prednisone resulted in an earlier improvement in the physical dimension of HR-QoL compared to placebo. Conclusion: We demonstrated that the PROQOL-HIV/TB scale adequately measures different aspects of self-reported HR-QoL in HIV-TB patients. Although more research is needed to understand how other domains related to HR-QoL can be improved, targeting patients at high risk for developing TB-IRIS with a four-week course of prednisone has a beneficial effect on the physical aspects of patient-reported quality of life.